The Bajau-Tainment: An AI-Powered Puzzle Game for Learning the Bajau Language Using Finite State Machine and Shuffle Techniques - Aulia Khoirunnita; Rasni Alex; Rosmasari Rosmasari (Politeknik Pertanian Negeri Samarinda, 2024)
The research titled